2023
DOI: 10.3390/ma16175832
|View full text |Cite
|
Sign up to set email alerts
|

Field Investigation of the Dynamic Response of Culvert–Embankment–Culvert Transitions in a High-Speed Railway

Ping Hu,
Huo Liu,
Yi-Zhi Tang
et al.

Abstract: The stiffnesses of embankments and culverts differ in the transition sections of high-speed railways (HSRs) due to their different supporting conditions. The dynamic irregularity caused by the different stiffnesses makes this transition area the weakest part of high-speed railways. Graded crushed stone combined with 5% cement is typically used to fill the subgrade in these transition areas. Thus, three different particle size ratios of crushed stone were matched and tested regarding the construction parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(35 reference statements)
0
0
0
Order By: Relevance
“…Mei scrutinized the attributes of peak dynamic displacements occurring along the track and transition subgrade under the influence of heavy-haul trains through field dynamic testing [29]. Hu undertook field dynamic tests within the culvert-embankment-culvert transition zone, encompassing train operating speeds spanning 5-360 km/h, and revealed that the train axle weight and travel direction exerted a more pronounced influence on the sections and layers within the immediate vicinity [30]. Huang executed field-monitoring tests within the context of the foam-concrete roadbed-culvert transition zone in a ballast railway and derived the relationship between the thickness of the foam-concrete layer and the dynamic response parameters [31].…”
Section: Introductionmentioning
confidence: 99%
“…Mei scrutinized the attributes of peak dynamic displacements occurring along the track and transition subgrade under the influence of heavy-haul trains through field dynamic testing [29]. Hu undertook field dynamic tests within the culvert-embankment-culvert transition zone, encompassing train operating speeds spanning 5-360 km/h, and revealed that the train axle weight and travel direction exerted a more pronounced influence on the sections and layers within the immediate vicinity [30]. Huang executed field-monitoring tests within the context of the foam-concrete roadbed-culvert transition zone in a ballast railway and derived the relationship between the thickness of the foam-concrete layer and the dynamic response parameters [31].…”
Section: Introductionmentioning
confidence: 99%